APPLICATION OF QUIZIZZ AS AN EVALUATION MEDIA ON TOPIC OF DIGESTIVE SYSTEM - Salwa Rezeqi; Desti Santi Natalia Pasaribu; A Aryeni (Universitas Negeri Medan, 2022)
This study examined to find out the review of media experts, teachers, and students on Quizizz and the increase of student learning outcomes to the application of Quizizz in 11th grade of Public high school majoring in science at SMA Negeri 1 Sumbul. The population of this study was 11th grade science students. The sample used in this study was 61 students using simple random sampling technique. The method used a descriptive mixed method. Data were collected using questionnaires and interviews, and student grade lists. The results showed that the application of Quizizz had received a score of 71 (good category) from media experts, a score of 91,2 (excellent category) from the teacher, a score of 94 (excellent category) from students, and N-Gain scores in student learning outcomes of 0,71 (high category). The highest N-Gain score was on the indicator of determining the nutritional content contained in foodstuffs by conducting a food test.